Evaluation of swab pooling and transport medium to improve the identification of avian influenza viruses in farmed ostriches in South Africa - Abolnik, Celia (University of Pretoria, 2020)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2019.